STANDAR OPERASIONAL PROSEDUR (SOP) SEBAGAI UPAYA PENINGKATAN PRODUKSI BAGI PELAKU UMKM AGRITEPA ABADI DESA BANJARSARI KABUPATEN BOGOR - Yuppy Triwidatin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Micro, Small and Medium Enterprises, known as MSMEs, have many roles in poor members, reduce unemployment, and increase people's income so that they can independently support their economy. UMKM players must be able to develop and survive in line with the intense business competition. The ability to compete in trade is important so that the Indonesian economy remains strong, especially in facing the Asean Economic Community (AEC). Therefore the government continues to strive so that MSMEs in various regions can develop so as to support the economy of the small community by providing various things both in terms of marketing, other supporting facilities. The presence of the 4.0 industrial revolution has an impact on intense competition, MSMEs must be able to overcome this view creatively, product innovation, marketing, product packaging, human resource development and technology. The strategy for empowering MSMEs can be achieved through the role of the Government in issuing fiscal and non-fiscal policies, higher education institutions in carrying out services to educate and prosper the community and the supporting role of supporting MSMEs to be more self-reliant and innovative. Community service is focused on UMKM Adritepa Abadi, Banjarsari Village, Bogor Regency, is able to prepare Standard Operating Procedures (SOP) and is able to make plans in the budget for running a business.